Modeling soil water and salinity dynamics in mangrove swamp rice production system of Guinea Bissau, West Africa - Gabriel Garbanzo; Maria do Rosário Cameira; Paula Paredes; Marina Temudo; Tiago B. Ramos (Agricultural Water Management)
Mangrove swamp rice production (MSRP) is of fundamental importance for the livelihoods, food security, and nutritional well-being of coastal populations in West Africa. However, this system faces increasing challenges due to its reliance on sufficient and well-distributed rainfall to maintain feasible soil salinity levels for rice production during the growing season. This study examines the dynamics of soil water and salts using field observations collected from four different MSRP fields in Guinea-Bissau during two growing seasons, along with simulations using the HYDRUS-1D model. Several rainfall and groundwater depth scenarios were also considered to identify the key factors contributing to soil salinity at the study sites. The results helped identify the main factors influencing soil salinity during the study period and estimate the potential impacts on crop yields, with could decline by up to 60 %. Key factors influencing soil salinity included the amount and distribution of seasonal rainfall, groundwater depth, and groundwater quality. The analysis of modeled scenarios also provided insights into effective management strategies for coping with soil salinization, particularly by assessing: a) where and when more productive, long-cycle rice varieties can still be cultivated; b) where salt-tolerant rice varieties have to be chosen. Additionally, the results reinforce the need for the regular maintenance of dikes and other drainage structures to avoid brackish water entrance and guaranty minimum rice growth conditions. Future research will explore adopting this practice in field with modern water management, with the model enabling precise analysis of impact on sustainability.